Evaluation of the morphology of pterygoid hamulus using cone beam computed tomography: A retrospective study - K. Smrithy Sivadas; Vidya Ajila; Shruthi Hegde; Yashika Jain (Journal of Oral Biology and Craniofacial Research)
Introduction: The pterygoid hamulus develops from the medial lamella of the pterygoid process. Understanding the architecture of the pterygoid Hamulus is crucial in terms of image interpretation as well as to diagnose idiopathic pain of the oral cavity and pharynx. Apart from diagnostic implications, the pterygoid hamulus can be utilised in forensic identification by studying its variations in different age groups and genders using three-dimensional imaging modalities such as cone beam computed tomography. Materials and methods: In this study, 608 Full FOV CBCT images were evaluated for the length, width, inclination, and shape of the pterygoid hamulus on both right and left sides in 4 different age groups, i.e. 20-30, 31–40, 41–50, and 51–60 years and correlated between males and females. Results: Statistically significant data was obtained with the assessment of pterygoid hamulus length, width, and inclination in the age groups spanning from 20 to 60 years. The distribution of shapes, i.e., slender and triangular, was found to be statistically significant in the assessed age groups. Males had a significantly longer and wider pterygoid hamulus compared to females. No statistically significant data were obtained on mean inclination and shape distribution among males and females. Conclusion: The assessment of various parameters of pterygoid hamulus using radiographic imaging modalities such as cone beam computed tomography could help in diagnosing orofacial pain of uncertain origin as well as in forensic identification, given variations noticed with age progression and amongst males and females.